PEMBERDAYAAN BADAN USAHA MILIK DESA DI DESA WANAHERANG KECAMATAN GUNUNG PUTRI KABUPATEN BOGOR - Rame Soekarsono; A. H. Rahadian; Prima Puruhita; Erni Prasetiyani; Munir Saputra (Institut Ilmu Sosial dan Manajemen Stiami, 2021)
The development of Village-Owned Enterprises (BUMDes) is important to obtain Village Funds. With business motivation training, digital digital era business development and basic accounting training to managers of Village-Owned Enterprises (BUMDes), it is hoped that they can increase BUMDes income. Implementation of Community Service and Service (PkM) by providing business motivation material, digital business insight material and interactive basic accounting training and inviting participants to directly practice. The PkM will be held for 4 hours on Wednesday, November 27 2019 in Wanaherang Village, Gunung Putri District, Bogor Regency. The training participants consisted of BUMDes managers, youth leaders and PKK representatives. The results of PkM show new enthusiasm and insight in the business world in the digital era as well as provide new knowledge in simple recording of business results to facilitate financial reporting